(untitled) (Bangladesh Journal of Zoology, 2010)
A study was conducted to adapt fish culture technology in the homestead seasonal ponds of coastal fishermen community of Cox’s Bazar with four approaches, viz. monoculture of GIFT (Genetically Improved Farmed Tilapia) strain of Oreochromis niloticus without supplementary feeding (T1), monoculture of GIFT with supplementary feeding (T2), mixed culture of GIFT and silver barb (Barbodes gonionotus) without supplementary feeding (T3) and with supplementary feeding (T4) each with three replications. After six months of rearing, the study revealed that production of fishes was significantly the highest (3,299.38 kg/ha) in T4, followed by 2,425.33 kg/ha in T3. Production of both monoculture treatments of 1,240.63 kg/ha in T1 and 1,406.96 kg/ha T2 were significantly lower than those of both mixed culture treatments (T3 and T4). The gross return was also the highest (1,58,221.67 Tk/ha) with the cost benefit ratio of 2.33 in T4. Bangladesh J. Zool. 38(1): 61-70, 2010